Vitiligo. Diagnostic and therapeutic recommendations of the Polish Dermatological Society - Rafal Czajkowski; Waldemar Placek; Iwona Flisiak; Dorota Krasowska; Joanna Maj; Mariola Marchlewicz; Adam Reich; Hanna Wolska; Lidia Rudnicka (Termedia Publishing House, 2019)
Vitiligo is an idiopathic chronic dermatosis manifested by depigmented patches of skin due to the loss of normal pigment-producing cells (melanocytes) and pigment (melanin). The disease develops more commonly in genetically predisposed individuals affected by various adverse external and internal factors inducing cellular stress in melanocytes. Cellular stress activates autoimmune and autoinflammatory mechanisms leading to melanocyte destruction. The disorder affects 0.5-4.0% of the world population, with no predilection for either sex. Manifestations can appear at any age, however in more than half of patients vitiligo starts before the age of 20 years. The course of the disease is varied - from stable cases with small isolated vitiligo patches to the rapid progression of lesions resulting in large areas of the skin being affected. There are multiple methods of treating vitiligo including pharmacological and surgical modalities, and phototherapy. Another essential aspect is patient education. Available treatment methods do not always yield the expected therapeutic effect. The Recommendations contain information about the diagnosis of vitiligo, and describe the recommended therapeutic methods.